Notes on psychophysics - Vincze, Gyula; Szasz, Andras (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
We describe the Norwich-Wong generalization of the Weber-Fechner law in the framework of a complex, self-controlling, self-similar feedback mechanism to ensure the condition of dendritic democracy